Memórias e narrativas : o percurso de escolarização e formação de professores(as) e alunos(as) dos anos finais da educação básica - Oliveira, Sandra Mara Vieira (2021)
This research discusses the school and formative memories of teachers and students of the final years of Basic Education, anchored in the experience of writing themselves. Its main objective was to analyze the course of education and training of these social subjects, in the direction of allowing the knowledge of oneself, of the other and the reflection on their practices through their narratives. In the field of Education, the relationship between teacher and student presents itself as a challenging theme, and from this perspective, social research has an important role in the study of social relationships built in the classroom space. The biographical method was the option for the epistemological and methodological support of this study and its uniqueness lies in the fact that it allows the researcher better access to the memory records of teachers and students. This research, of a quali-narrative nature, was carried out in the form of a case study, privileging autobiographical narratives as the guiding instrument for data collection with teachers and students from Colégio Modelo Luís Eduardo Magalhães (CMLEM) in Itapetinga – BA. The social subjects of the research were three professors, twenty-four students from the 3rd year of high school and the general director. The data collection period was from October 2018 to November 2019. For the analysis and interpretation, hermeneutics was used as methodology, in the interpretative – comprehensive perspective of Ricoeur (2013). This study provided teachers and students with other perspectives on their formative paths and a survey of possibilities in view of the new paths that are presented. Initially, the research analyzed the interlacing between school education and human education, anchoring on the premise that the human being is complete in the relationship with the other and in this perspective Education must contribute to the humanization. Then talked about social memory and what motivates the human being to remember, and what prevents him from (re) visiting, dealing with the records of this memory through the narrative of himself and the reading of the other. Thus, when thinking of the word as a training tool, the teaching knowledge and the training process were analyzed, as well as the youth knowledge and the schooling process. In the course of writing, the school space, the locus of the materiality of this study, was presented, as well as the collaborating teachers and students. Finally, the threads of the narratives of teachers and students about their school and training experiences were woven. The teachers talked about the contributions and difficulties that school life imposed and when narrating their trajectories, they teach us that the human is made in the walk with the other, in the relationships that bend in the fabric of the encounters and mismatches of life. In the students, the experience of writing and talking about themselves left as a legacy the importance of being heard and also listening, in the midst of so many students silenced in their school trajectories. This research has as main theoretical framework: Abrahão, Arendt, Arroyo, Bolívar, Delory-Momberger, Dominicé, Ferraroti, Finger, Flick, Freire, Gondar, Halbwachs, Ricoeur, Romão, Saviani, Tardiff and Wolton.